1997
DOI: 10.1111/j.1741-6612.1997.tb01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Computers Enhancing the Lives of Older People

Abstract: A survey of 312 older people was conducted to ascertain the extent to which they use modern devices, and their attitudes towards modern technology. Although respondents expressed interest in new technology and confidence in learning to use modern devices, few owned or used a computer. Based on these findings, the “Seniors‐On‐Line” program was established with the aim of providing older people with the opportunity to enhance their lives through the use of computers. Participants were aged from 55 to 89. Teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 8 publications
3
10
0
2
Order By: Relevance
“…Women have previously been found to be less likely than men to have positive attitudes towards computers, to have higher levels of computer anxiety and, consequently, to be less likely to use computers or the Internet as frequently as men (Bimber, 2000;Irizarry& Downing, 1997;Karavidas et al, 2005). Our data support these findings.…”
Section: Discussionsupporting
confidence: 93%
“…Women have previously been found to be less likely than men to have positive attitudes towards computers, to have higher levels of computer anxiety and, consequently, to be less likely to use computers or the Internet as frequently as men (Bimber, 2000;Irizarry& Downing, 1997;Karavidas et al, 2005). Our data support these findings.…”
Section: Discussionsupporting
confidence: 93%
“…34 The South Australian research found that older people use computers for record-keeping ( 48% of the sample, two years after completion of a course), letter-writing ( 45%) and for writing memoirs and stories (12%). 35 While the proportions differ, the results reported here show similar interests. There is a substantial difference with results from US studies, however.…”
supporting
confidence: 61%
“…12 Irizarry and Downing too suggest that lack of opportunity rather than lack of desire, interest or motivation, is what separates many older people from the benefits of computer technology, and go on to promote its introduction in a supportive environment to this sector of the population. 13 While older people are slower than other groups to accept computer-based sources of information for everyday life 14 -research has shown that they do not readily seek information from formal sources but rely mainly on informal sources and established contacts 15 -they can be very positive about computers once they are offered hands-on experience. 16 However, 'the reality of living in the Information Age is that most people in future are going to need some level of IT literacy' .…”
mentioning
confidence: 99%
“…) 。しかし近年では,日々の生 活に対する満足感や幸福感といった感情的な側面だ けでなく,自己の肯定的な受容や自己実現,豊かな 対人関係の構築などといった人生の意味に対する満 足度や充実感を反映する心理的ウェルビーイングの あり方も重視されるべきであるとして,主観的ウェ ルビーイングを多次元的に捉えようとする見方が主 流になりつつある (Ryff, 1989;Waterman, 1993 (Loyd & Gressard, 1987;Shashaani, 1993) ,性差の影響がないと する研究も散見される (Powell, 2013;Whitely, 1997 Karavidas et al(2005) (Irizarry & Downing, 1997;Kay, 1989;Shashaani, 1993 Loyd & Gressard, 1987;Shashaani, 1993 …”
unclassified